Cross Validation can Cause a Difference of Misinterpretation to Valid Interpretation (Global Journal of Human-Social Science, 2016)
Easy availability of remote sensing dataset increases its importance and use by multiple folds, especially in areas of rough and difficult terrain like snow bound mountains. But at the same chances of misinterpretations will also be increased in the same proportion, when dealing with high altitude mountains in remote sensing. Seasonal variation within single year time framework and temporal changes in long time are more important to understand separately. Verification of the imagery selection, operations and findings is the key of analysis. This paper focused upon misinterpretation often occurs in the geospatial domain by shifting the focus, when observations transforming to information. A negligible error in selection of imagery, operation or perception make it possible to misinterpret the findings. In this study we are try to withdrawing kind attention of users toward small-small negligence, that cost a lot. In this study we take area under Nanda Devi national Park as an example to highlight such errors.
Keywords: accuracy assessment; cross validation; land use land cover; change detection; remote sensing and misinterpretation